Time-varying importance measure of mechanical systems considering maintenance. Issue 9 (11th November 2019) - Li, Yangfan; Zhang, Yingjie; Zhang, Lin; Dai, Bochao
Abstract : Purpose: The purpose of this paper is to analyze the changes in its importance due to the maintenance and repair of components. Design/methodology/approach: In this paper, a concept of time-varying importance measure is proposed to solve the problem of component importance change caused by maintenance. When the system is broken-down, the probability difference between the component works well after repairing and the component break down before repairing is solved, this difference is measured as an index of time-varying importance method. Then, the approach has been verified by the CNC machine tool. Findings: The paper provides a method to analyze the importance of changes of components in the system due to maintenance. The time-varying importance measure can evaluate the component importance anytime during its whole life span, and it has the ability to find out the most responsible component for a system failure in the actual production process. What is more, it provides guidance for the next maintenance work. Originality/value: The proposed method can guide the next maintenance time according to the change of component performance caused by each maintenance activity of the manufacturing system, and avoid the waste of resources caused by repeated maintenance.